1999
DOI: 10.1086/314641
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Virus Load and Perinatal Human Immunodeficiency Virus Type 1 Subtype E Transmission, Thailand

Abstract: To determine the rate and risk factors for human immunodeficiency virus (HIV)-1 subtype E perinatal transmission, with focus on virus load, pregnant HIV-infected women and their formula-fed infants were followed prospectively in Bangkok. Of 281 infants with known outcome, 68 were infected (transmission rate, 24.2%; 95% confidence interval, 19.3%-29.6%). Transmitting mothers had a 4.3-fold higher median plasma HIV RNA level at delivery than did nontransmitters (P<.001). No transmission occurred at <2000 copies/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0
6

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 125 publications
(58 citation statements)
references
References 38 publications
0
52
0
6
Order By: Relevance
“…4 Despite increasing availability of antiretroviral treatment for HIV-infected children, illness and death caused by the progression of perinatal HIV infection will place a substantial burden on the health care system in Thailand. Caring for these HIVinfected children requires an understanding of the manifestations of perinatal HIV infection in Thailand, where most HIV infections in children are with subtype E. 5 Knowing the expected duration of survival after perinatal infection helps with counseling families of HIV-infected children. Identifying predictors of disease progression can help indicate prognosis and guide treatment.…”
Section: T He Epidemic Of Perinatal Human Immunodeficiency Virus (Hivmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Despite increasing availability of antiretroviral treatment for HIV-infected children, illness and death caused by the progression of perinatal HIV infection will place a substantial burden on the health care system in Thailand. Caring for these HIVinfected children requires an understanding of the manifestations of perinatal HIV infection in Thailand, where most HIV infections in children are with subtype E. 5 Knowing the expected duration of survival after perinatal infection helps with counseling families of HIV-infected children. Identifying predictors of disease progression can help indicate prognosis and guide treatment.…”
Section: T He Epidemic Of Perinatal Human Immunodeficiency Virus (Hivmentioning
confidence: 99%
“…The enrollment procedures for this study and analysis of perinatal transmission have been published. 5,6 The study was conducted before the AIDS Clinical Trials group 076 study ended 7 ; antiretroviral prophylaxis was not yet used to prevent mother-infant transmission, although HIVinfected mothers were advised not to breastfeed and were provided infant formula and ongoing infant feeding counseling. During the course of this study, primary prophylaxis against Pneumocystis carinii pneumonia (PCP) was not used routinely for HIV-exposed infants, but was used for children with signs of HIV infection.…”
Section: Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Joint United Nations Programme on HIV/AIDS, approximately 58% of HIV-infected individuals in sub-Saharan Africa are women and 9% are children (29). Both sexual and perinatal transmission of HIV are associated with a high plasma viral load (10,14,20,23,25,27,28).…”
mentioning
confidence: 99%
“…The levels of systemic virus, as measured by HIV-1 RNA in plasma, have been shown to predict the rate of disease progression (9,12,17,18). Moreover, studies in the United States and Thailand have shown that maternal plasma HIV-1 RNA levels are highly correlated with the risk of infant infection (3,5,13,20). Recently, it has been shown that individuals with higher plasma viral RNA levels are significantly more likely to sexually transmit HIV-1 than individuals with lower plasma viral RNA levels (19).…”
mentioning
confidence: 99%